AN ANALYSIS OF TEACHER’S STRATEGIES IN TEACHING ENGLISH - Mustika, Ulfiatul; Wardah, Wardah (Journal of English Education Program, 2021)
This research was conducted to analyze what strategies the teachers have used in teaching English and what factors influence these strategies. This was a descriptive qualitative research for the English teacher of SMAN 1 Segedong. Data collection was carried out using interviews with an English teacher at the school. Data were analyzed using Familiarization and Organizing, Coding and Reducing, Interpreting and Representing. Based on research findings, there were five teaching strategies used by the teacher and three factor influence it. These strategies were discussion strategies, demonstration strategies, using electronic media as learning media, using games and providing reinforcement in the end teaching and learning process. There were three factors that influenced the teacher strategy in English at SMAN 1 Segedong. The first was the student factor which includes the background of the student's majors such as Science and Social Studies, and the student's condition in following the learning process. The second was the factor came from the teacher. This factor concerned the ability of teachers to use technology in supporting teaching strategy. Lastly, the facility includes how the learning tools are limited.